A Legal Analysis of Drug Abuse Among Teenagers - Adit Hartadi; Alip Rahman; Anom Sutrisno (International Journal Labs, 2026)
This study attempts to examine criminal policies related to the drug problem in Indonesia, especially among adolescents. The author employs a qualitative research method and a juridical-normative approach by studying information from library sources through legal documents, covering both Class I and Class II substances. This study applies a descriptive-analytical approach, in which the descriptive method is used in the initial stage to present argumentation, while the analytical method is used to determine the extent of the gap between legal values and norms in theory and in legal practice. Accordingly, this research is classified as normative research. The study shows that criminal policy measures in Cirebon City have a fairly sound legal basis, grounded in Law Number 35 of 2009, Law Number 11 of 2012, and Cirebon City Regional Regulation Number 11 of 2023. Policy steps are described in terms of those that regulate criminal acts, as well as those that address non-criminal approaches, integrated in the form of rehabilitation, diversion, restorative justice, and prevention programs in families, schools, and communities. However, these measures must be improved, particularly in terms of consistency in the operationalization of field assessments concerning the best interests of adolescent development and rehabilitation.